Communicating with Social Imaginary: Cultural Identities, Popular TV Fiction, and Audience Responses - Mohd Muzhafar Idrus; Ruzy Suliza Hashim; Raihanah Mohd Mydin (2024)
Since the turn of the 21st century, popular TV fiction in Malaysia has been thriving, popular, and critically-acclaimed due to their extensive local, national reach. Drawing more than one million viewers including staggering online reruns, this sheer popularity of some popular TV fiction has led to the questioning of issues that viewers can relate to. In this paper, we contextualize popular TV fiction within a space of cultural identities, focusing on audience-response analysis. Specifically, we argue that these popular TV fiction permit audience to communicate with images of social imaginary as seen in Julia, Adam & Hawa, and On Dhia, articulating issues related to controversies and taboo such as alcoholism and cohabitation. Through diverse audience voices captured from interviews and personal narratives, we will show how their reactions reveal the intricacies of dealing with Malay subjectivities. By telling their stories, we also show how these audience responses may reflect cracks and fractures, between what is supposed to be shown and the reality in which these expectations are translated in popular TV fiction.